The role of the American corporate media in U.S. policy: framing Hezbollah - Long, Benjamin (AUC Knowledge Fountain, 2012)
The American corporate media has proven to play a significant role in U.S. policy formation. Operating as a member of the power elite, as defined by C. Wright Mills, the corporate media serve the crucial functions of creating, implementing, and maintaining politically motivated policies sought to serve the parochial interests of the power elite. Disrupting a critical element of democracy â providing the public with the information needed for intelligent discharge of ones political responsibilities â the corporate media, filtered by a â guided-market system,â operate to â inculcate and defend the economic, social, and political agenda of privileged groups that dominate the domestic society and the state.â Developing this â guided-market systemâ within their Propaganda Model (PM), Noam Chomsky and Edward Herman have provided an abundance of data displaying this function of the corporate media. The PM is utilized in this thesis, testing the corporate media's role in sustaining and maintaining U.S. policy toward the Shi'a organization, Hezbollah. This thesis argues that the current policy toward Hezbollah, defined by it's designation on the U.S. State Department Foreign Terrorist Organization (FTO) list, is outdated, yet maintained by the corporate media serving the interests of the power elite. The PM states that where there is consensus among the power elite, the corporate media will offer its unconditional support for its chosen policy by creating narrow parameters for debate, or the bounds of â thinkable thought,â and marginalizing any and all voices of dissent. The â leftâ or â liberalâ boundary of debate will be set by what is perceived to be the â liberalâ media. This thesis conducted a content analysis of the â liberalâ corporate media outlet, the New York Times, and its coverage of Hezbollah. Further, in order to argue that the current policy is outdated, yet maintained by the corporate media serving the interests of the power elite, this thesis included a historical analysis of Hezbollah, an investigation into the political nature of the FTO designation process, and the interests of the power elite that guides the outdated policy. The findings demonstrated that the New York Times consistently supported the current policy and never questioned its validity. Further, the Times remained silent on all voices of dissent, marking out the left, liberal parameter. This thesis proved that the current U.S. policy toward Hezbollah is outdated, yet maintained by the corporate media operating as a significant member of the power elite.